LES MARTOVYCH’S OPEN JOURNALISM: ISSUES, CONTEXT, GENRES AND MOTIVES - Марчук, Г. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
Publicistic works by Les Martovych were researched. The peculiarities of the writer’s worldview formation and development of his social and political views were analyzed. The main attention is focused on the ideological and thematic and genre-stylistic features of publicistic works of the writer; the key trends of his journalism and its close connection with the social and literary process of the late nineteenth - early twentieth century and with artistic creativity of the satirist were identified.